2015
DOI: 10.1111/1346-8138.13214
|View full text |Cite
|
Sign up to set email alerts
|

Safety profiles and efficacy of infliximab therapy in Japanese patients with plaque psoriasis with or without psoriatic arthritis, pustular psoriasis or psoriatic erythroderma: Results from the prospective post‐marketing surveillance

Abstract: A large-scale prospective post-marketing surveillance was conducted to evaluate the safety and efficacy of infliximab in Japanese patients with plaque psoriasis, psoriatic arthritis, pustular psoriasis and psoriatic erythroderma. This study was conducted in all psoriasis patients treated with infliximab after its Japanese regulatory approval. Infliximab was administrated at 5 mg/kg at weeks 0, 2 and 6, and every 8 weeks thereafter. Patients were serially enrolled and observed for 6 months to evaluate the safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 35 publications
4
39
4
1
Order By: Relevance
“…However, we could not clarify whether elevated serum IFX level by dose escalation resulted in increased AE or not, because serum IFX level in onset time of each AE was not evaluated. In contrast, the incidences of AE, SAE and infections in this study were similar to those reported in Japanese post-marketing surveillance of standard-dose of IFX therapy, 17 and the safety profiles were consistent with those in previous studies, 8,9 raising no new safety concerns. In addition, no correlation of trough serum IFX level with occurrence of AE was observed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…However, we could not clarify whether elevated serum IFX level by dose escalation resulted in increased AE or not, because serum IFX level in onset time of each AE was not evaluated. In contrast, the incidences of AE, SAE and infections in this study were similar to those reported in Japanese post-marketing surveillance of standard-dose of IFX therapy, 17 and the safety profiles were consistent with those in previous studies, 8,9 raising no new safety concerns. In addition, no correlation of trough serum IFX level with occurrence of AE was observed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…IL-17A promotes the expression of TNF-α by keratinocytes (19), which indicates that the above-mentioned TNF-α/IL-23/IL-17 axis likely forms a vicious loop in the development of psoriasis lesions (Figure). The mechanistic hypothesis coincides with the fact that antibodies against TNF-α, IL-23(p19), IL-23(p40), IL-23R, IL-17A or IL-17RA exert remarkable clinical effects on psoriasis both in Caucasian and Asian ethnicities (8, 22-31). In contrast, the decisive pathogenic roles of IL-12, IFN-γ and IL-22 in psoriasis remain elusive, as clinical trials of the anti-IL-12 p35-p40 antibody (SMART), anti-IFN-γ antibody (HuZAF) and anti-IL-22 antibody (fezakinumab) have been discontinued (8).…”
Section: Pathogenesis Of Psoriasissupporting
confidence: 66%
“…Table 1 shows the list of biologics available for psoriasis in Japan. In the References section, the following are listed as sources for efficacy and safety data in pivotal studies of each biologic in and outside of Japan and for the results of Japanese post-marketing surveillance of each biologic: infliximab, [7][8][9][10][11][12][13][14][15][16] adalimumab, 17-23 ustekinumab, 24-32 secukinumab, [33][34][35][36][37][38][39][40][41][42] ixekizumab, [43][44][45][46][47][48] brodalumab, [49][50][51][52][53][54] guselkumab, 55-61 risankuzumab 62-64 and infliximab BS. 65,66 Additional note: Psoriasis arthropathica and psoriatic arthritis.…”
Section: Patients With Generalized Pustular Psoriasis (Gpp)mentioning
confidence: 99%